Immediate vaginal and perineal reconstruction after abdominoperineal excision using the Inferior Gluteal Artery Perforator Flap (V-IGAP). Issue 1 (January 2022) - Johal, Kavan S.; Mishra, Ankit; Alkizwini, Eman; Whitehouse, Harry; Batten, Gemma; Hachach-Haram, Nadine; Lancaster, Katie; Constantinides, Joannis; Mohanna, Pari-Naz; Roblin, Paul; Ross, David A.
Summary: Background: The fasciocutaneous inferior gluteal artery perforator (IGAP) has been previously demonstrated to be a robust reconstructive choice after abdominoperineal excision (APE), with comparably low morbidity relative to other flaps. In patients who undergo concurrent vaginectomy, we demonstrate in this retrospective cohort study how IGAP modification allows simultaneous vaginal reconstruction with a favourable complication profile and long-term return to sexual activity. Methods: Oncological resection was completed with the patient prone. Unilateral or bilateral IGAP flaps may be used based on vaginal defect size and surgeon preference. In this study, important features of flap design, mobilisation and inset are presented, together with a retrospective cohort study of all cases who underwent vaginal reconstruction. Clinical outcomes were determined by the length of stay, early to late complications, and quality of life assessment including a return to sexual function. Results: Over a 10-year period, 207 patients underwent abdominoperineal resection (APE) in our cross-centre study (86% subject to neoadjuvant chemoradiotherapy), with 22/84 female patients electing for vaginal reconstruction (19 partial, 3 total vaginectomies). Minor complications were observed in 6/22 cases, with two patients progressing to healing after-theatre debridement (major). The median follow-up time was 410 days. Quality of life questionnaires reported high patient satisfaction, with 70% of patients returning to sexual activity. Conclusions: For patients undergoing APE with concurrent vaginectomy, the IGAP flap can be used alone for both perineal dead space management and neovaginal reconstruction, negating the need for an alternative second flap and avoiding significant donor morbidity. This study shows excellent long-term clinical outcomes, including a return to sexual activity.